Dietary beliefs among informal caregivers regarding common childhood diseases in rural north-west India - Gupta, Rajiv Kumar; Verma, Aruna; Raina, Sunil K; Kumari, Rashmi; Langer, Bhavna; Gupta, Chandni; Akhter, Najma (Indian Journal of Community Health, 2017)
Background: Dietary practices among infants and children are predictor of their growth and development. India being a huge of diverse cultures, diversity in beliefs and practices regarding diet during childhood illnesses is expected. Harmful beliefs and practices can contribute to malnutrition among children. These beliefs can have adverse consequences in already sick children. Aims and Objectives: To assess the dietary knowledge, beliefs and practices of rural care givers during childhood illnesses. Material & Methods: This cross-sectional descriptive study was conducted among 271 rural informal (parent / family member) caregivers in one of the sub-health centres which was selected using simple random sampling technique. In the context of this study, the word informal care-giver was used for parent/family member of the child, preferably a mother with a child / children aged less than five years. The survey tool was an open ended and pretested questionnaire which was developed by public health expert’s familiar with the culture of the study setting and was pilot tested before administration. For the purpose of recruiting the study participants a house to house survey was conducted and the data thus collected was analyzed in percentages. Results: Informal Caregivers had low knowledge of common childhood illnesses as well as the reasons of their causation. Majority of them consulted a doctor in the event of child’s illness. 53.81% reduced feeding and 31.93% diluted diet during child’ illness but significantly 77.85% didn’t change breastfeeding practice during illness. As far as the beliefs regarding dietary practices were concerned, it found that egg, meat, chicken and jaggery were labelled hot foods while curd, butter milk and vegetables were labelled as cold foods. Rice water and khichadi were preferred in diarrhoea but spicy food and milk were restricted. Ginger and Tulsi tea were preferred in respiratory infections while ice-cream and curd / milk were withheld. Conclusion: Hot and cold beliefs regarding foods are firmly rooted in the study population, so dietary education has a key role to play but it has to be within socio-cultural milieu of the people. It is imperative to train medical and para-medical staff in nutrition curriculum to promote healthy eating habits in the population